ANALISIS CERITA RAKYAT ASAL-USUL SEMARANG DALAM MENANAMKAN PENDIDIKAN KARAKTER PADA SISWA SEKOLAH DASAR - Evi Nur Azizatun Muniroh; Rida Fironika Kusumadewi; Sari Yustiana (Institut Daarul Qur'an Jakarta, Indonesia, 2024)
The problems found in SDN Karangroto 02 Semarang related to the knowledge of folklore about the origin of Semarang is still very low, this is what is the reference for a study related to literature review based on folklore in various regions to instill character education. The purpose of this study is to instill students' character skills related to the folklore of the origin of Semarang. The novelty in this study is related to the story of the origin of Semarang by using various interesting media during the learning process. The research method used is a qualitative literature review, where data collection uses various articles related to character building based on regional folklore that is still related to the origin of Semarang. The data collection technique in this study compares various existing articles, whether various similar articles are capable of increasing character building in students. The results of the review of various existing articles have experienced a lot of good understanding related to character building in students related to story analysis. It can certainly be concluded that the analysis of the folklore of the origin of Semarang is able to instill character education in elementary school students.